Modeling Credit Contagion via the Updating of Fragile Beliefs - Benzoni, Luca; Collin-Dufresne, Pierre; Goldstein, Robert S.; Helwege, Jean (Review of Financial Studies, 2015)
We propose an equilibrium model for defaultable bonds that are subject to contagion risk. Contagion arises because agents with “fragile beliefs” are uncertain about the underlying economic state and its probability. Estimation on sovereign European credit default swaps (CDS) data shows that agents require a time-varying risk premium for bearing state uncertainty. The model outperforms affine specifications with the same number of state variables, suggesting that there are important nonlinearities in credit spreads that are captured by our model. Contagion drives most of the variation in CDS spreads, especially before the crisis. However, economic fundamentals account for a significant fraction during the crisis.